Complications of acute myocardial infarction in women over 50 years of age in a coronary unit - Costoyas, Diego Javier; Minghetti, Marcelo (Salud Integral y Comunitaria, 2024)
Introduction: cardiovascular diseases are the main cause of mortality in women around the world. Erroneously for many years it was considered a disease of men and therefore they were the most studied in terms of risk factors, symptoms, treatments and complications. Ischemic heart disease mainly affects postmenopausal women because by decreasing the estrogen load, cardiovascular risk increases. Therefore, we will study the characteristics of acute myocardial infarction in women over 50 years of age to learn about this highly prevalent disease from another gender. Material and methods: for this study we will carry out an observational,retrospective, cross-sectional and analytical investigation. At the Instituto Cardiovascular de Buenos Aires, collecting information from the medical records of female patients over 50 yearsof age with acute myocardial infarction in the period May- July 2022. Results: of 22 patients analyzed in this study, 19 of them successfully survived the cardiovascular event and only 3 had fatal consequences. These patients, who were between the ages of 53 and 94 (with almost 50 % of them between the ages of 70 and 80) had comorbidities at the time of the coronary event. 72 % had high blood pressure, while only 18 % had diabetes. In the interview we found that 77 % of them led a sedentary life, 36 % were smokers, and 22 % had suffered a previous myocardial infarction. When performing the admission electrocardiogram, 36 % revealed ST-segment elevation while 63 % presented ST-segment depression. The treatment of choice in 36 % of the patients was transluminal coronary angioplasty within the first hour of admission, while 63 % received the same treatment on a scheduled basis in the following days. Conclusion: based on what was analyzed in this study, transluminal coronary angioplasty is the treatment with the highest success rate for acute-stage infarction, because it is a minimally invasive procedure and has a low mortality rate. Sometimes when performed together with the placement of a stent, the percentage of recurrence decreases since the artery is kept patent. Its main objective is to restore blood flow to the heart tissue with the intention of preventing a more complex procedure.